Motor cortex transcriptome reveals microglial key events in amyotrophic lateral sclerosis - Oriol Dols‐Icardo; Víctor Montal; Sònia Sirisi; Gema López‐Pernas; Laura Cervera‐Carles; Marta Querol‐Vilaseca; Laia Muñoz; Olivia Belbin; Daniel Alcolea; Laura Molina‐Porcel; Jordi Pegueroles; Janina Turón‐Sans; et al. (2020)
Objective To identify transcriptomic changes, neuropathologic correlates, and cellular subpopulations in the motor cortex of sporadic amyotrophic lateral sclerosis (ALS). Methods We performed massive RNA sequencing of the motor cortex of patients with ALS (n = 11) and healthy controls (HCs; n = 8) and analyzed gene expression alterations, differential isoform usage, and gene coexpression networks. Furthermore, we used cell type deconvolution algorithms with human single-nucleus RNA sequencing data as reference to identify perturbations in cell type composition associated with ALS. We performed immunohistochemical techniques to evaluate neuropathologic changes in this brain region. Results We report extensive RNA expression alterations at gene and isoform levels, characterized by the enrichment of neuroinflammatory and synaptic-related pathways. The assembly of gene coexpression modules confirmed the involvement of these 2 major transcriptomic changes, which also showed opposite directions related to the disease. Cell type deconvolution revealed an overrepresentation of microglial cells in ALS compared with HC. Notably, microgliosis was driven by a subcellular population presenting a gene expression signature overlapping with the recently described disease-associated microglia (DAM). Using immunohistochemistry, we further evidenced that this microglial subpopulation is overrepresented in ALS and that the density of pTDP43 aggregates negatively correlates with the proportion of microglial cells. Conclusions DAM has a central role in microglia-related neuroinflammatory changes in the motor cortex of patients with ALS, and these alterations are coupled with a reduced expression of postsynaptic transcripts.